Berbelanja Melalui Jasa Titip Perabot di Masa Pandemi Covid-19: Studi Kasus @jastipbyarumi - Musdalifa Tul Jannah (Universitas Muslim Maros, 2021)
In the digital era, deposit service (jastip) which were previously carried out offline, are now also developing and can be done by online and become a very promising business. In Indonesia, the term jastip by shopping online is starting to be widely known by the wider community, especially for those who use social media, such as Facebook. This business benefits from a predetermined additional fee for each consumer ordered goods, so those who order goods do not need to go to the store to buy goods or leave the house. Buying goods online through jastip has become increasingly popular during the Covid-19 pandemic, especially since the government launched large-scale social restrictions (PSBB) that limit people's mobility. This research was conducted on social media, namely Facebook on jastip providers and consumers based on observations on social media, such as Facebook, which showed the widespread purchase of goods through jastip among women in Bulukumba Regency. There are them women involved in this study. Thye are varied based on age (between 23 and 40 years), occupation (five housewives, four entrepreneurs, and jastip provider), and status (nine buyers and a jastip provider). The results of this study indicate that jastip of Informa products is the choice among mothers who are purchased online through a jastip service provider posted through social media Facebook. Among other jastip items on Facebook, home furnishings (sofa, dining table, patio chairs, etc.) are the most popular items. Model, status display, price, and quality are four main reasons why women choose Informa's jastip products, especially during this Covid-19 pandemic. The increase in the use of jastip during the Covid-19 pandemic is intertwined with an increase in jastip turnover (@jastipbyarumi 9). The reason for the jastip provider (@jastipbyarumi) presenting jastip product is because women in Bulukumba Regency love to shop online, and Informa is the most popular products among women. Thus, this is seen by jastip provider as a business opportunity, a way of satisfying hobbies, and as a source of income. In promoting jastip, the strategies used by jastip provider are promoting products along with its discounted price, uploading products in stories, and opening social gathering lots. In running such service business, the main capital is not money itself, but most importantly trust, perseverance, and business ethics.